If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(2x + -1) = 48 Reorder the terms: -8(-1 + 2x) = 48 (-1 * -8 + 2x * -8) = 48 (8 + -16x) = 48 Solving 8 + -16x = 48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -16x = 48 + -8 Combine like terms: 8 + -8 = 0 0 + -16x = 48 + -8 -16x = 48 + -8 Combine like terms: 48 + -8 = 40 -16x = 40 Divide each side by '-16'. x = -2.5 Simplifying x = -2.5
| 1/3x-28 | | 6a-5=133 | | 4(x+8)=2 | | 7(4-1k)= | | -3w+31=-8w+56 | | -5(x-1)=5 | | (2m-11)/-3=-9 | | 9(y+8)=2 | | (x+5)=70 | | 10=2+2y | | 12x+7y=15.5 | | X/140= | | 8(w+4)=10 | | -10-6x=14-7x | | Y/7=3.5 | | 5x+12=(6x)-(10) | | 5(-10x-2)= | | 140=7/15=X | | -x+34=75 | | 27x+7=81 | | 8(w-4)=4 | | 4q^2-3q=3q^2-6q+28 | | 6a+-5=133 | | 2/8×3 | | (4s-5)(5)= | | 4q^2-3q=3q^2-6q | | 8(w-4)=2 | | (3x+7)+(7x+3)=180 | | 2x=360-180 | | 53=-9x | | -9x+9(-4)=-18 | | 12x-10=395 |